Wewenang dan Tanggungjawab Lembaga Manajemen Kolektif Nasional (LMKN) Dalam Perlindungan Hak Ekonomi Musisi Indonesia - Vira Nur Maharani; Dwi Desi Yayi Tarina (Jurnal Interpretasi Hukum, 2024)
Currently, there are many musicians who use songs without permission from their creators. This phenomenon of copyright infringement is increasing in the music industry, where industry players use music and songs owned by creators for commercial purposes without permission and without paying the rightful royalties. As a result, many disputes arise between musicians. One example of a case involving music royalties and licensing is the dispute between Ahmad Dhani and former Dewa 19 vocalist, Once Mekel. This conflict arises because Once Mekel is suspected of singing Dewa 19 songs without permission from Dhani and without permission from the Indonesian Collective Management Organization for Music (LMK WAMI). The case was resolved through non-litigation mechanisms by reaching a peaceful agreement between both parties. The agreement allows Once to sing only one Dewa 19 song titled "Cemburu," while Once states that he will not sing any other Dewa 19 songs until an unspecified time limit. This issue raises questions about the responsibilities and authority of the National Collective Management Organization (LMKN) as the institution managing musicians' royalties in Indonesia. In relation to this issue, LMKN has created the website lmknlisensi.id as a response to this controversy. This study uses a normative legal research method with a statute approach and data analysis technique in the form of descriptive analysis. This article is expected to serve as a reference for relevant parties to enhance understanding and protection of musicians' economic rights in Indonesia.